A Critical Analysis of Educational Technology in The Era of Industrial Revolution 4.0 - Meindra, Pimpin; Wahyono, Hari (Classroom Action Research Journal (CARJO), 2020)
Education is one of the most important things to create a generation of people who are ready for the changing times. It takes careful preparation in preparing good education through learning that illustrates the current condition of the world. This study aims to determine the tasks and roles of teachers, the use of learning resources and media in economic learning and the way teachers respond to change, the role of schools in facilitating economic learning, the education system applied in economic learning, and the impact on students. This research method is included in qualitative research with an active participatory research approach. The resource persons of this study were the teachers of Malang State High School 8, grade X and XI, four students with two students from class X and two students from class XI, Waka Curriculum, and Waka Facilities and Infrastructure. The instrument used in this study was the Observation Result Sheet and interviews. The results of this study indicate that there are teacher tasks that include teacher pedagogical and administrative tasks as well as implementation in learning, teacher learning resources and media, the role of school institutions that have provided facilities in the form of webmasters and internet bandwidth that have been enlarged, the education system that has referred to the education system the latest, and the impact on students varies depending on the learning style carried out by the teacher.Â How to Cite